2019
DOI: 10.1002/ep.13198
|View full text |Cite
|
Sign up to set email alerts
|

Improving the water production of a solar still by adding an internal condensation chamber: A theoretical study

Abstract: In this article, the validity of a numerical simulation of a basin solar still coupled with a condensation chamber was analyzed, before being cooled through a cooling water system. The system contained a serpentine pipe combined with a rectangular sheet of galvanized steel. The model was validated by comparing calculated and then experimental results mentioned in previous research for a typical day in the month of June 2013, the comparison of results showed a good agreement between the experimental and numeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…3,5,6 The yield of a conventional solar still normally lies between 2 and 5 L m À2 per day. 3,4,7 To overcome this bottleneck, researchers conducted numerous studies on different design parameters of solar still, like, the effect of tilt of still, 8,9 depth of saline water, 10 different geometric modifications, [11][12][13] shading, 14 and evaporative fans 15 for its productivity enhancement.…”
Section: Status Of Solar Still Technology: Active and Passive Solar D...mentioning
confidence: 99%
See 2 more Smart Citations
“…3,5,6 The yield of a conventional solar still normally lies between 2 and 5 L m À2 per day. 3,4,7 To overcome this bottleneck, researchers conducted numerous studies on different design parameters of solar still, like, the effect of tilt of still, 8,9 depth of saline water, 10 different geometric modifications, [11][12][13] shading, 14 and evaporative fans 15 for its productivity enhancement.…”
Section: Status Of Solar Still Technology: Active and Passive Solar D...mentioning
confidence: 99%
“…Evaporation heat transfer occurs between water mass and the inner glass surface. Evaporation heat transfer can be calculated using Equation (12).…”
Section: Mathematical Modeling and Performance Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of condensation can be enhanced by reducing temperature of the condensing cover. Kerfah et al 126 reported enhancement in the water productivity with the addition of an internal condensation chamber. Hassan and Elfadl 127 experimentally tested four types of condensing elements namely, an aluminum plate, a heat sink of aluminum with pin fins, glass, and a plate of aluminum covered with an umbrella.…”
Section: Parameters Influencing Water Productivity Of the Solar Stillsmentioning
confidence: 99%
“…His results indicated that using this technique increases the distillate yield of the still to 43%. It is also agreed that the cooling water flow rate can produce opposite effects, which is studied by the newly developed model 18 that evaluates the performance of the system throughout the year. It was concluded that the cumulative yield of the still was sensitive to the flow mass of cooling water, which changes annually according to meteorological conditions.…”
Section: Introductionmentioning
confidence: 99%